An in-vitro comparison of canal debridement efficiency between three systems of Rotary, Reciprocal and Vertical - Sheykhrezaee MS.; Eshghyar N.; Farzaneh B.; Ashofteh Yazdi K. (Tehran University of Medical Sciences, 2004)
Statement of Problem: Total removal of tissues and remnant microorganisms as well as canal shaping are the essential objectives of endodontic therapy. A successful endodontic treatment is obtained through Shilder's principals, however; complete observation of this technique using stainless steel files manually is problematic and time-consuming. Modern technology, in order to eliminate such problems, has presented new facilities such as Nickel-Titanium (NiTi) files and engine driven instruments. Purpose: The aim of this in-vitro study was to compare the canal debridement efficiency of three engine driven instruments: Rotary, Reciprocal and Vertical. Materials and Methods: In this experimental study, 60 mesial roots of human first and second mandibular molars were divided into three groups randomly. In each sample, one canal was considered as case, the other one as control. Files used in Reciprocal and vertical groups were of handy Ni-Ti type and in rotary group, rotary Ni-Ti files were used. After debridement, the roots were sectioned at 3mm and 5mm from anatomic apex, stained and examined under light microscope. Comparison criteria between case and control groups were based on residual debris and predentin and the level of root canal preparation and shaping after debridement. Data were subjected to kruskal-Wallis non-parametric test. Results: There was no significant difference between the efficiency of debridement at 3mm and 5mm sections between all groups. But difference in time consumption was significant ranked from the shortest to the longest as rotary, reciprocal and vertical. Conclusion: The efficiency of debridement between the three automated instruments was approximately equal, however; the instrumentation time was different between three groups. Rotary system was the fastest one, as compared with reciprocal (second) and vertical (last). It may be concluded that rotary system has a superiority over the other two groups in conventional root canal therapies.